Baroque architecture : 1600-1750 - Frederique, Lemerle; Pauwels, Yves. ([S.l.] : Flammarion, 2008)
This book, beautifully illustrated and written by two authorities on sixteenth- and seventeenth-century art and architecture, leads the reader through the major styles and shifts of baroque architecture throughout Europe and beyond, and provides a fascinating account of how baroque developed in relation to the unique urban culture of each nation where the style became popular. To admire the undulating façade of Rome s San Carlo alle Quattro Fontane, to walk through the Palace of Versailles lavish succession of rooms, or to marvel at the seemingly endless array of columns and windows of St. Petersburg s Winter Palace is to observe architecture in the act of glorifying the key powers of the day the empire, wealth, the church, and even mankind s inventiveness. In-depth coverage of the architecture of France and Italy is coupled with serious analysis on how the style developed in Spain, Portugal, Poland, Russia, and Scandinavia, as well as in the Spanish and Portuguese colonies in the Americas.Giving the richest and most complete account of its history to date, this is an essential introduction to baroque architecture for the general reader.
Keywords: Architecture; Architecture, Baroque; Europe